“Watch out, organize, inform yourself!”: Tracing the Dynamics of Twitter Discourse on Anti-Nazi Street Protests - Dang-Anh, Mark; Eble, Michael (AoIR Selected Papers of Internet Research, 2013)
With the advent of mobile devices, mediatized political discourse became more dynamic. I assume that the microblog Twitter can be considered as a medium for spatial coordination during protests. Therefore, the case of neo-Nazi demonstrations and counter-protests in the city of Dresden that occurred in February 2012 is analysed. Data consists of microposts that occurred during the event. Quantitative analysis of hashtag and retweet frequencies was performed as well as qualitative speech act pattern analysis and a tempo-spatial discourse analysis on selected subsets of microposts. Results show that a common linguistic practice is verbal georeferencing and by that constructing space. Empirical analysis indicates a strong relation between communicational online space and physical offline place: Protest participants permanently reconfigure spatial context discursively and thus the contested protest area becomes a temporarily meaningful place.